Analisis Dampak Kondisi Sosial Ekonomi Keluarga terhadap Tingkat Minat Belajar Anak Prasekolah (3-6 Tahun) di KB Darussalam Sidoarjo - Shofiyatuz Zahroh; Nailatun Nahdiyah (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to analyze the impact of family socio-economic conditions on the interest in learning of preschool children (ages 3-6) at KB Darussalam Sidoarjo. Interest in learning at an early age is an important foundation for children's cognitive and socio-emotional development in the future. However, this interest does not exist in isolation but is greatly influenced by the child's immediate environment, namely the family and its socio-economic conditions. Abraham Maslow's Hierarchy of Needs theory is used as a conceptual framework to understand how the fulfillment of children's basic needs, which is often related to socio-economic conditions, affects their motivation and interest in learning. This study employs a qualitative approach with a case study design, focusing on KB Darussalam Sidoarjo. Data is collected through in-depth interviews with parents/guardians and teachers, as well as participatory observation of children in the learning environment. The research results show that the socio-economic conditions of families have a significant and multifaceted impact on the learning interest of preschool children. Economic limitations can hinder the fulfillment of children's physiological needs and their sense of safety, which directly reduces their energy and focus on learning. In addition, socio-economic conditions affect the quality of parent-child interactions and the availability of learning stimulation at home, which are crucial to fostering a sense of love, belonging, and appreciation in children. An environment that inadequately supports basic needs tends to result in lower levels of interest in learning.